Race for Profit: How Banks and the Real Estate Industry Undermined Black Homeownership by Keeanga-Yamahtta Taylor - Adam Butz; Christopher Burks (Journal of Social Equity and Public Administration)
This piece is a review of the heralded book, Race for Profit: How Banks and the Real Estate Industry Undermined Black Homeownership (2019, The University of North Carolina Press). While Taylor’s Race for Profit has been widely praised among reviewers in disciplines like history, urban planning, and business administration, its lessons have not been fully unpacked for the field of public administration. We first highlight important and relevant sections of the book, then discuss lessons for social equity and public administration.